Outcomes of early parent‐child adrenocortical attunement in the high‐risk offspring of depressed parents. Issue 4 (12th March 2018) - Merwin, Stephanie M.; Barrios, Chelsey; Smith, Victoria C.; Lemay, Edward P.; Dougherty, Lea R.
Abstract: This study examined the impact of parent‐child attunement of morning cortisol on parenting and child outcomes in dyads with and without parental depression. Participants included 142 parent‐child dyads (3–5 years‐old) who provided morning cortisol samples at Wave 1, and 98 dyads returned for the 3‐year follow‐up at Wave 2. Results indicated that for parents with a history of depression and for female children, stronger attunement predicted increases in parental hostility from Wave 1 to Wave 2. For females only, stronger attunement was related to children's depressive symptoms at Wave 1 and Wave 2. Stronger attunement was also associated with increases in children's depressive symptoms from Wave 1 to Wave 2, poorer psychosocial functioning at Wave 1, and ADHD symptoms at Wave 2. Findings highlight attunement as an important biological process related to parenting and child outcomes and suggest it may play a role in the intergenerational transmission of depression risk.